THE APPLICATION OF RECIPROCAL STRATEGY TO INCREASE STATE ISLAMIC SENIOR HIGH SCHOOL (MAN) STUDENTS’ READING COMPREHENSION - Nopiati Nopiati; Santi Mayasari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: This research is aimed at finding out whether or not there is a significant difference on students’ reading comprehension achievement between those who are taught by using reciprocal strategy and those who are not. The result shows that students’ reading comprehension achievement of the experimental group has higher mean score than the students of the control group. Furthermore, based on the independent t-test score (22.67) with the sig. value 0.898, it is found that the use of reciprocal strategy is effective. This can also be meant that there is a significant difference on students’ reading comprehension achievement between those who are taught by using reciprocal strategy and those who are not. This can be stated that reciprocal strategy brings positive impact on MAN students’ reading comprehension achievement.Keywords: reciprocal strategy, senior high students, reading comprehension